Problematika Pemindahan Gereja GKI di Bogor Barat - Siti Nurbaeti Sajiah; Banun Binaningrum; Syarifah Rusydah (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This research discusses Polemic on the Impact of the Relocation of the GKI Church at the Congregational Post Court in West Cilendek, West Bogor, which involves social, cultural, and its impact on relations between residents. The main focus of the research is the understanding of church and congregation policies, as well as the influence of church displacement on community identity and social cohesion. A qualitative methodology with a sociological approach is used in this study through interviews, document studies, and observations. The results of the study show that people accept church relocation to maintain social stability, strengthen interfaith relationships, and improve public services. The Mayor's policy of supporting an inclusive atmosphere has succeeded in making the new church a center of social activities that strengthens solidarity between religious communities, thanks to intensive communication, constructive dialogue, and the role of religious leaders as mediators.